-2(12a-8)=-5(a+8)-5a

Simple and best practice solution for -2(12a-8)=-5(a+8)-5a equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(12a-8)=-5(a+8)-5a equation:


Simplifying
-2(12a + -8) = -5(a + 8) + -5a

Reorder the terms:
-2(-8 + 12a) = -5(a + 8) + -5a
(-8 * -2 + 12a * -2) = -5(a + 8) + -5a
(16 + -24a) = -5(a + 8) + -5a

Reorder the terms:
16 + -24a = -5(8 + a) + -5a
16 + -24a = (8 * -5 + a * -5) + -5a
16 + -24a = (-40 + -5a) + -5a

Combine like terms: -5a + -5a = -10a
16 + -24a = -40 + -10a

Solving
16 + -24a = -40 + -10a

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '10a' to each side of the equation.
16 + -24a + 10a = -40 + -10a + 10a

Combine like terms: -24a + 10a = -14a
16 + -14a = -40 + -10a + 10a

Combine like terms: -10a + 10a = 0
16 + -14a = -40 + 0
16 + -14a = -40

Add '-16' to each side of the equation.
16 + -16 + -14a = -40 + -16

Combine like terms: 16 + -16 = 0
0 + -14a = -40 + -16
-14a = -40 + -16

Combine like terms: -40 + -16 = -56
-14a = -56

Divide each side by '-14'.
a = 4

Simplifying
a = 4

See similar equations:

| -140=4(6x+7) | | 4(3+8m)=12+8m | | 18x+3(4x-9)=-6x+81 | | 3X+9Y=-18 | | x-3/8-1=x-7/9 | | 8=11p+13 | | 9x^2+23x+4=0 | | -4(p+2)+8=2p(p-1)-7p+15 | | -104=8(p-8) | | 2.3(5-x)=-0.7(1-x) | | -2.05x+1.8(x-3)=6.2 | | -10p-3=-1+2(3p-9) | | X+x+42=180 | | 4x+72-4x=27x-21-4x | | 3x-13=8x+22 | | 6x-3y-4z=-15 | | 15=-20x | | 30x^2+55x+15= | | -27-3x=-x^2+1 | | x+3+4-8=5+7x | | 5(-4+3b)=-125 | | 45t=-30 | | 5n+9=4-4(2n-11) | | 1/3(1-x)-(x+1)/2=-2 | | 6.46+2.3x=1.24x-7 | | 129=3(1+7v) | | .2y-3=.5 | | G(-2)=4(-2)-3 | | (9x-3)/6=5/2 | | y/5-7=-2 | | t^2/2+t^2 | | 13a-45+a= |

Equations solver categories